Synthesis and Characterization of ZnO Thin Film for Modeling the Effect of Its Defectson ZnO/Cu2O Solar Cell EQE - Chala, S.; Boumaraf, R.; Bouhdjar, A.F.; Bdirina, M.; Labed, M.; Taouririt, T.E.; Benbouzid, Y. (Sumy State University, 2021)
Zinc oxide (ZnO) is one of the best transparent conducting oxide (TCO) materials with a wide bandgap and good electrical and optical properties. Its low cost, nontoxicity and transparency in the optical region of the electromagnetic spectrum make it very promising candidate for solar cell applications. In this work, zinc acetate precursor was used to grow a ZnO thin film by using sol-gel spin-coating technique. The surface morphological study using scanning electron microscope (SEM) was carried out to confirm the growth pattern and crystal distribution. The optical properties, transmission (T), reflection (R), optical bandgap (Eg), refractive index (n), and extinction coefficient (k) were extracted and investigated to be used in the simulation of ZnO/Cu2O heterostructure solar cell, where ZnO thin film plays a double role: as the TCO window, as well as the emitter of the n-p junction. However, the solar cell showed weak external quantum efficiency (EQE) compared to those prepared by using zinc nitrate and diethyl zinc precursors. TCAD numerical simulation was used to clarify the origin of this weak EQE by taking into account two parameters. The first studied parameter is the root-mean-square interface roughness, CRMS, in Haze modeling approach, H, which describes how much of incident light is scattered at the interface. The second studied parameter is the density of defects in the ZnO bulk with continuous distribution of states in its bandgap similar to an amorphous semiconductor made of tail bands and Gaussian distribution deep level bands. Consequently, and by adjusting and investigating the effect of the CRMS and the constituents of the bandgap states, we were able to obtain a good agreement between simulated and measured EQE characteristics of the solar cell. ©2021 Sumy State University.All rights reserved.
Keywords: Defects; EQE; Simulation; Sol-gel; ZnO/Cu2O Solar Cell.